Condition monitoring method for running bogies using vibration isolators with built-in piezoelectric element - Shogo MAMADA; Tatsuya OHTA; Shinichi SAGA; Kazuhiro YOSHIKAWA (Nihon Kikai Gakkai ronbunshu, 2023)
The axle spring vibration isolator rubber installed on the axle box that encloses the axle bearings is subjected to loads corresponding to the wheel weight and vibration of the axle box during running. It is thought that the running condition of the bogie can be monitored by utilizing the axle spring vibration isolator rubber as a sensor to grasp the load and vibration. Therefore, we investigated a method of monitoring the running condition of the bogie by incorporating a piezoelectric element, which generates electric signals in response to applied loads and vibrations, in the axle spring vibration isolator rubber. In this paper, we made the rubber isolator with a built-in piezoelectric element (RIBP). As a result of running tests with the RIBP installed on a bogie, we found that the running condition of the bogie can be monitored by the time waveform of the electrical signal obtained from the piezoelectric element, and that the condition of the axle bearing can be monitored by the result of frequency analysis. In addition, as a result of examining the actual method of monitoring the running condition of a bogie using a RIBP, it was found that the condition could be monitored even if the number of RIBP installed on the bogie was reduced.